A case report: Intermittent catheterization combined with rehabilitation in the treatment of carbapenem-resistant Klebsiella pneumoniae catheter-associated urinary tract infection - Shen, Lihua; Wu, Heng; Chen, Huiying; Jiang, Yan (Frontiers in Cellular and Infection Microbiology, 2022)
Catheter-related urinary tract infections, especially those caused by multidrug-resistant (MDR) bacteria, are extremely difficult to treat due to limited therapeutic choices. Therefore, removing catheters as soon as possible is pivotal to successful treatment. Herein, we report a case of catheter-related urinary tract infection caused by carbapenem-resistant Klebsiella pneumoniae (CRKP). Intermittent catheterization was used to reduce biofilm occurrence and exercise bladder function on the basis of an active and adequate anti-infection strategy. Simultaneously, combined with acupuncture treatment and strengthening the patient’s pelvic floor muscle training to improve urinary retention, the catheter was eventually removed to obtain autonomous urination in this patient, and this led to the successful treatment for a CRKP catheter-related urinary tract infection.